Gliotoxin-mediated bacterial growth inhibition is caused by specific metal ion depletion - Downes, Shane G.; Owens, Rebecca A.; Walshe, Kieran; Fitzpatrick, David A.; Dorey, Amber; Jones, Gary W.; Doyle, Sean (Scientific reports, 2023)
Overcoming antimicrobial resistance represents a formidable challenge and investigating bacterial growth inhibition by fungal metabolites may yield new strategies. Although the fungal non-ribosomal peptide gliotoxin (GT) is known to exhibit antibacterial activity, the mechanism(s) of action are unknown, although reduced gliotoxin (dithiol gliotoxin; DTG) is a zinc chelator. Furthermore, it has been demonstrated that GT synergises with vancomycin to inhibit growth of Staphylococcus aureus . Here we demonstrate, without precedent, that GT-mediated growth inhibition of both Gram positive and negative bacterial species is reversed by Zn 2+ or Cu 2+ addition. Both GT, and the known zinc chelator TPEN, mediate growth inhibition of Enterococcus faecalis which is reversed by zinc addition. Moreover, zinc also reverses the synergistic growth inhibition of E. faecalis observed in the presence of both GT and vancomycin (4 µg/ml). As well as zinc chelation, DTG also appears to chelate Cu 2+ , but not Mn 2+ using a 4-(2-pyridylazo)resorcinol assay system and Zn 2+ as a positive control. DTG also specifically reacts in Fe 3+ -containing Siderotec™ assays, most likely by Fe 3+ chelation from test reagents. GSH or DTT show no activity in these assays. Confirmatory high resolution mass spectrometry, in negative ion mode, confirmed, for the first time, the presence of both Cu[DTG] and Fe[DTG] 2 chelates. Label free quantitative proteomic analysis further revealed major intracellular proteomic remodelling within E. faecalis in response to GT exposure for 30–180 min. Globally, 4.2–7.2% of detectable proteins exhibited evidence of either unique presence/increased abundance or unique absence/decreased abundance (n = 994–1160 total proteins detected), which is the first demonstration that GT affects the bacterial proteome in general, and E. faecalis , specifically. Unique detection of components of the AdcABC and AdcA-II zinc uptake systems was observed, along with apparent ribosomal reprofiling to zinc-free paralogs in the presence of GT. Overall, we hypothesise that GT-mediated bacterial growth inhibition appears to involve intracellular zinc depletion or reduced bioavailability, and based on in vitro chelate formation, may also involve dysregulation of Cu 2+ homeostasis.